A Comparative Analysis of Women's Property Rights in Jewish Law and Anglo-American Law - Kofsky, Alina Semo (Journal of law and religion, 1988)
Woman is a slave, from the cradle to the grave. Father, guardian, husband—master still. One conveys her, like a piece of property, over to the other.—Ernestine RoseIn the past several decades there has been a growing movement within the Jewish community to improve the self-image and status of women in Halachah (Jewish law). There is no doubt that this movement was largely affected by the women's liberation movement that has been taking place since the beginning of this century. Despite the assertion of many rabbis and scholars that the role of women in traditional Judaism has been noticeably superior to that of other contemporary civilizations, critics frequently point to the many religious activities from which women continue to be excluded. In the past, women were not accepted as witnesses in a trial; did not inherit equally with their male siblings; were not required or expected to perform the daily religious duties assigned to men; and had to sit separately from the males in the congregation. Only recently have Jewish women been ordained as rabbis and relied on as cantors; allowed to serve on congregational boards as presidents of congregations; granted equal access to study, and allowed to perform all mitzvot; counted in a minyan, the quorum needed for a public worship service, and called to the pulpit for aliyot during the Torah service; and able to ignore the formal requirement of providing a get, the bill of divorce, although it can still be requested.